PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS SOSIAL DAN TENAGA KERJA KOTA MEDAN - Hasrudy Tanjung (JURNAL ILMIAH MANAJEMEN & BISNIS, 2015)
This study aimed to determine the effect of work discipline and motivation to work on the performance of employees at the Department of Social Welfare and Labor of Medan. Population and sample of this study were employees of the Department of Social and Labor Medan, amounting to 94 people. Data collection techniques used in this study is a list of questions (questionnaire), which consists of five options with Likert scale, the study documentation and interviews (interviews). While the techniques of data analysis in this study uses the classical assumption test, multiple linear regression, t-test, f, and the coefficient of determination. The results of this study concluded that jointly independent variables have an influence on the performance of employees. Of the two independent variables are variables work discipline has a greater influence terhadp employee job performance. Keywords : Performance, Decipline & Motivation